GC-MS-Based metabolite profiling of cosmos caudatus leaves possessing alpha-glucosidase inhibitory activity - Javadi, Neda; Abas, Faridah; Abdul Hamid, Azizah; Simoh, Sanimah; Shaari, Khozirah; Ismail, Intan Safinar; Mediani, Ahmed; Khatib, Alfi (Association of Food Scientists & Technologists, 2014)
Cosmos caudatus, which is known as “Ulam Raja,” is an herbal plant used in Malaysia to enhance vitality. This study focused on the evaluation of the α-glucosidase inhibitory activity of different ethanolic extracts of C. caudatus. Six series of samples extracted with water, 20%, 40%, 60%, 80%, and 100% ethanol (EtOH) were employed. Gas chromatography-mass spectrometry (GC-MS) and orthogonal partial least-squares (OPLS) analysis was used to correlate bioactivity of different extracts to different metabolite profiles of C. caudatus. The obtained OPLS scores indicated a distinct and remarkable separation into 6 clusters, which were indicative of the 6 different ethanol concentrations. GCMS can be integrated with multivariate data analysis to identify compounds that inhibit α-glucosidase activity. In addition,catechin, α-linolenic acid, α-D-glucopyranoside, and vitamin E compounds were identified and indicate the potential α-glucosidase inhibitory activity of this herb.